Sazonalidade em séries temporals quadrissemanais — o caso do IMEC (Economia Aplicada, 1999)
This paper uses the available econometric techniques to analyze the seasonality in the time series of the Indicator of Economic Movements (IMEC), measured by Fundayao Instituto de Pesquisas Economicas (PIPE), from Sao Paulo (Brazil). It is more plausible for this series to consider a model with a smooth transition in trend and intercept rather than the alternative hypothesis of a unit root. Taking these findings into account, we then searched for any type of typical seasonal behavior inside the month in the detrended time series.There is evidence of deterministic seasonality in the beginning of the month, with a positive impact in the first week and a negative impact in the second week. There is also evidence of periodic behavior, indicating a different response of the series dependent on the week that the observation occurs.